Recent Advances of Pharmaceutical Process Chemistry and Its Innovation in China: Part 1 - Tang, Pei; Nie, Biao; Huang, Jiuzhong; Zhang, Yingjun; Zhang, Ji; Chen, Fen-er (Pharmaceutical Fronts, 2020)
This review article summarizes recent developments and innovations in China's pharmaceutical process chemistry over the last several decades. Case studies of dozens of blockbuster drug processes are presented, including bulk drugs, such as the over-the-counter medicine biotin, demonstrating China's substantial effort to green its pharmaceutical processes. Owing to the increasing stringent environmental regulations, Chinese chemists have invented several cutting-edge and eco-friendly synthetic methods that are beneficial to environmental protection. Applied to large-scale industrial production, these processes have a greatly reduced environmental footprint, promoting the sustainable development of global economy and health.
Keywords: pharmaceutical industry; green process; asymmetric catalysis; chiral drugs; stereoselectivity